2003
DOI: 10.17986/blm.200382495
|View full text |Cite
|
Sign up to set email alerts
|

Çocuklarda Fatal Yabancı Cisim Aspirasyonları

Abstract: …ZET SUMMARYAs a very serious reason of accidental deaths in childhood, we have aimed to investigate deaths due to foreign body aspiration (FBA), since its incidence has not decreased despite advances in the techniques and instruments for its emergency treatment.We retrospectively reviewed the records of forensic cases due to FBA examined at the DiyarbakÝr Branch of the Council of Forensic Medicine between 1990 and 2003. Over this period this office investigated 8330 medicolegal deaths cases, 22 of which were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…[3] Goren et al studied the mortality in children in relation to FBA and reported that 36.4% of the victims were dead on arrival, 50% on intervention, and 13.6% after complications due to delayed hypoxia. [4] We studied and compared the morbidity and mortality in the early and late diagnosis groups of paediatric FBA presenting to our hospital.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Goren et al studied the mortality in children in relation to FBA and reported that 36.4% of the victims were dead on arrival, 50% on intervention, and 13.6% after complications due to delayed hypoxia. [4] We studied and compared the morbidity and mortality in the early and late diagnosis groups of paediatric FBA presenting to our hospital.…”
Section: Discussionmentioning
confidence: 99%
“…The nature of inhaled foreign bodies varies from country to country and is dependent on diverse cultural, social, and economic factors that include parental attitudes, eating habits, availability and types of potentially threatening objects, and prevention strategies [3][4][5][6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Aspiration of a foreign body (FB) into the tracheobronchial tree besides being serious due to risk of causing death by asphyxia [1,2], can also chronically lead to irreversible pulmonary lesions. Most FBs are aspirated by children under 10's [3], and over 50% of them are under 3's [4].…”
Section: Introductionmentioning
confidence: 99%